Triaxial mechanical behaviours of Ili loess after freeze–thaw - Chu, Chunmei; Yang, Longwei; Cheng, Wenyu; Wang, Juncheng; Wang, Xiang (Frontiers in Earth Science, 2024)
Loess is strongly sensitive to water, and its properties are substantially affected by weathering and other factors. Loess landslides, which are widely distributed in Ili, are closely related to seasonal freeze–thaw effects. In this study, multiple freeze–thaw cycle tests were conducted on loess samples with different moisture contents from the Ili region, and triaxial shear tests were conducted to study mechanical characteristics of the loess. Variations in the microstructure of the loess samples were analysed using scanning electron microscopy images to reveal the underlying mechanisms. The results showed that the freeze–thaw cycles significantly influence failure mode of the stress–strain curve of loess samples with a lower moisture content of 10%, which transitioned from strain softening to strain hardening with six cycles as the turning point, whereas the stress–strain curve transitioned from strong to weak hardening for the loess samples with higher moisture content of 18%. As the number of freeze–thaw cycles increased, failure strength and shear strength parameters of loess gradually decreased, and tended to stabilize after the 10th cycle. In addition, strength parameters deterioration is most significant after the first cycle, and the degree of cohesion deterioration was much greater than that of internal friction angle. Cohesion and internal friction angle showed attenuation exponential function and polynomial function relationship, respectively, with the number of freeze–thaw cycles, and their fitting parameters underwent a sudden change with increasing moisture content, with 14% as the turning point. Microscopic SEM revealed that the number of overhead pores increased, and point–to–point contact between particles increased after freeze–thaw, which was consistent with increase in of loess porosity. This revealed the fundamental reason for the significant deterioration in loess strength caused by freeze–thaw cycles.